Nitrogen-Sparing Mechanisms in Chlamydomonas Affect the Transcriptome, the Proteome, and Photosynthetic Metabolism. Issue 4 (18th April 2014) - Schmollinger, Stefan; Mühlhaus, Timo; Boyle, Nanette R.; Blaby, Ian K.; Casero, David; Mettler, Tabea; Moseley, Jeffrey L.; Kropat, Janette; Sommer, Frederik; Strenkert, Daniela; Hemme, Dorothea; Pellegrini, Matteo; et al.
Abstract : This work examines the mechanisms by which Chlamydomonas reinhardtii copes with nitrogen (N) limitation, finding transcriptomic and proteomic changes in multiple metabolic pathways and identifying an N-sparing mechanism that prioritizes respiratory metabolism and shifts the proteomic balance toward proteins with lower N contents, a result with implications for engineering of N-use efficiency. Abstract: Nitrogen (N) is a key nutrient that limits global primary productivity; hence, N-use efficiency is of compelling interest in agriculture and aquaculture. We used Chlamydomonas reinhardtii as a reference organism for a multicomponent analysis of the N starvation response. In the presence of acetate, respiratory metabolism is prioritized over photosynthesis; consequently, the N-sparing response targets proteins, pigments, and RNAs involved in photosynthesis and chloroplast function over those involved in respiration. Transcripts and proteins of the Calvin-Benson cycle are reduced in N-deficient cells, resulting in the accumulation of cycle metabolic intermediates. Both cytosolic and chloroplast ribosomes are reduced, but via different mechanisms, reflected by rapid changes in abundance of RNAs encoding chloroplast ribosomal proteins but not cytosolic ones. RNAs encoding transporters and enzymes for metabolizing alternative N sources increase in abundance, as is appropriate for the soil environmental niche of C. reinhardtii . Comparison of the N-replete versus N-deplete proteome indicated that abundant proteins with a high N content are reduced in N-starved cells, while the proteins that are increased have lower than average N contents. This sparing mechanism contributes to a lower cellular N/C ratio and suggests an approach for engineering increased N-use efficiency.